VISUAL PATTERN STRUCTURE INVESTIGATION BY CLUSTERING PACKAGE - Melnyk, Roman; Roman, Yuriy (International Journal of Computing, 2014)
The paper contains research results of graphic file format influence on image structure, quantitative changes in structuring coefficients of clustered images, influence of deformation changes caused by destruction processes on image quality. Clustering package for visual black-white and grey patterns was taken as the main instrument for investigation.